JAVANESE IDENTITY THROUGH SYMBOLIZATION OF CANTING: A STUDY OF THE NOVEL CANTING BY ARSWENDO ATMOWILOTO - Wahyu Handayani Setyaningsih; Wury Dwiwardani (Jurusan Sastra Indonesia, 2020)
This research takes novel Canting as the object of analysis. This research used cultural semiotics approach. The research aims to find the Javanese identity symbolized in canting. The results obtained as follows: (1) Javanese identity is represented by the attitude of